Expression of lipogenic markers is decreased in subcutaneous adipose tissue and adipocytes of older women and is negatively linked to GDF15 expression - Šrámková, Veronika; Koc, Michal; Krauzová, Eva; Kračmerová, Jana; Šiklová, Michaela; Elkalaf, Moustafa; Langin, Dominique; Štich, Vladimír; Rossmeislová, Lenka (Journal of physiology and biochemistry, 2019)
In aging, the capacity of subcutaneous adipose tissue (SAT) to store lipids decreases and this results in metabolically unfavorable fat redistribution. Triggers of this age-related SAT dysfunction may include cellular senescence or endoplasmic reticulum (ER) stress. Therefore, we compared lipogenic capacity of SAT between young and older women and investigated its relation to senescence and ER stress markers. Samples of SAT and corresponding SAT-derived primary preadipocytes were obtained from two groups of women differing in age (36 vs. 72 years, n = 15 each) but matched for fat mass. mRNA levels of selected genes (lipogenesis: ACACA, FASN, SCD1, DGAT2, ELOVL6; senescence: p16, p21, NOX4, GDF15; ER stress-ATF4, XBP1s, PERK, HSPA5, GADD34, HYOU1, CHOP, EDEM1, DNAJC3) were assessed by qPCR, protein levels of GDF15 by ELISA, and mitochondrial function by the Seahorse Analyzer. Compared to the young, SAT and in vitro differentiated adipocytes from older women exhibited reduced mRNA expression of lipogenic enzymes. Out of analyzed senescence and ER stress markers, the only gene, whose expression correlated negatively with the expression of lipogenic enzymes in both SAT and adipocytes, was GDF15, a marker of not only senescence but also mitochondrial dysfunction. In line with this, inhibition of mitochondrial ATP synthase in adipocytes strongly upregulated GDF15 while reduced expression of lipogenic enzymes. Moreover, adipocytes from older women had a tendency for diminished mitochondrial capacity. Thus, a reduced lipogenic capacity of adipocytes in aged SAT appears to be linked to mitochondrial dysfunction rather than to ER stress or accumulation of senescent cells.
Keywords: buněčná diferenciace; Mitochondria; chaperon endoplazmatického retikula BiP; Stress of endoplasmic reticulum; Humans; Senescence; Endoplasmic Reticulum Chaperone BiP; stárnutí buněk; Female; Aged; dospělí; stárnutí; lipogeneze; senioři; lidé; mitochondrie; Biomarkers; Lipogenesis; Aging; Adipocytes; Adult; Subcutaneous Fat; Mitochondrial dysfunction; tukové buňky; biologické markery; ženské pohlaví; Subcutaneous adipose tissue; stres endoplazmatického retikula; Endoplasmic Reticulum Stress; Cell Differentiation; Cellular Senescence; růstový diferenciační faktor 15; Growth Differentiation Factor 15; podkožní tuk